A modeling study of the effect of an alternating magnetic field on magnetite nanoparticles in proximity of the neuronal microtubules: A proposed mechanism for detachment of tau proteins. (July 2022) - Mohammadi, Simah; Rafii-Tabar, Hashem; Sasanpour, Pezhman
Highlights: The effect of alternating magnetic field was investigated on microtubule and tau protein via induced thermal and mechanical stresses. Mechanical effects including lorentz force and maxwell stress tensor were investigated on magnetite nanoparticle inside the magnetic field. Magnetite nanoparticles could induce microtubule deformation when exposed to alternating magnetic field. Toroidal magnetic coil generates higher magnetic flux density compared to the other shapes of coil. Abstract: Background and objective: It is known that the disintegration of microtubules in neurons occurs in response to the phosphorylation of the tau proteins that promotes the structural instability of the microtubules, as one of the factors underlying the onset of Alzheimer's disease (AD). Methods: In this study, the mechanical variations undergone by the tau protein's and microtubule's structures due to the action of intrinsic magnetite nanoparticles inside the brain tissue have been computationally modeled using the finite element (FEM) method. Results: The von Mises stress induced by magnetite nanoparticles, subject to an applied alternating magnetic field, leads to local heating and mechanical forces, prompting a corresponding deformation in, and displacement of, the microtubule and the tau protein. Conclusions: The induction of these deformations would increase the probability of the microtubules' depolymerization, and hence their eventual structural disintegration. Graphical abstract: Image, graphical abstract